Characterization of a light-regulated gene encoding a new phycoerythrin-associated linker protein from the cyanobacterium Fremyella diplosiphon. - Federspiel, N A (1992)
Cyanobacteria utilize multimeric protein complexes, the phycobilisomes, as their major light-harvesting antennae. Associated with the chromophorylated phycobiliproteins in these complexes are nonpigmented proteins, designated linker proteins. These linker proteins are believed to mediate assembly of the phycobilisome and energy transfer to the photosynthetic reaction center. We cloned and sequenced a gene, cpeE, encoding a previously uncharacterized linker protein which is expressed in green light in Fremyella diplosiphon. This gene is part of an operon containing two other phycoerythrin-associated linker genes, cpeC and cpeD. Transcription of the cpeCDE operon in green light results in two predominant species of mRNA of approximately 2,100 and 3,200 nucleotides. The shorter transcript encodes only CpeC and CpeD, while the longer contains the coding regions for all three linker proteins. By altering the pH of the resolving gel and the running buffer during sodium dodecyl sulfate-polyacrylamide gel electrophoresis, this third linker protein CpeE can be resolved from the rod-core linker and the other rod linker proteins. The three proteins have an overall similarity of approximately 62%, and the genes encoding the three proteins are approximately 59% identical.